Audit Kinerja dan Peningkatan Akuntabilitas Publik: Lampiran ISSAI 3100 - Boby Segah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
The existence of a Performance Audit can increase public accountability and provide opportunities for Audit Institutions (in Indonesia: the Supreme Audit Agency) to make a real contribution to improving efficiency and effectiveness in the implementation of public administration. This guide aims to create things that can benefit Audit Institutions that carry out Performance Audit as well as important issues that need to be considered in implementing and establishing a joint implementation of a Performance Audit at an Audit Agency. This concept is primarily aimed at Senior Managers and Employees in Audit Institutions, so that they understand the requirements and challenges faced. Directing the strategies needed and the impacts that arise due to the implementation or functioning of a Performance Audit that is carried out on an ongoing basis. Audit institutions carry out different forms and authorities. The size and organizational culture also vary. Therefore it is not possible to produce detailed guidelines that apply to all Audit Institutions; then this document focuses on the challenges of the strategy relating to the resources needed and the process of implementing Performance Audit. Also highlighted are the main features of Performance Audit and their benefits for Audit Institutions, public administration processes and society as a whole.